Alcoholic Hand Sanitizer on the Incident of Contact Dermatitis in Health Workers - Rianto, Louis; Tanzia, Sherren; Agatha, Priscilla Clara; Celine, Celine; Octavianus, Daniel (GLOBAL HEALTH SCIENCE GROUP, 2024)
The COVID-19 pandemic has increased the frequency of using alcohol-based hand sanitizers, especially among health workers. This increase in the frequency of using hand sanitizers increases the incidence of contact dermatitis. The presence of allergens and reduced fat and water content in the skin causes contact dermatitis. This research was conducted to review more deeply how much influence the use of hand sanitizers has on the incidence of contact dermatitis for health workers in the COVID-19 era and to provide advice on the use of additional materials as well as the selection of materials and procedures for using hand sanitizers to reduce the incidence of contact dermatitis. A literature search was conducted from journal articles with a time span of 2012-2022 using databases in the form of Pubmed, Ebsco, Google Scholar, Hindawi, Medline and Science Direct (65 articles). We included 65 research articles that met the inclusion and exclusion criteria by analyzing the abstract and full text through tables together. Research shows that the use of alcohol-based hand sanitizers with high frequency and contains allergenic ingredients triggers the occurrence of contact dermatitis in health workers. So the use of additional ingredients such as moisturizers and the selection of alcohol-based hand sanitizer materials must be considered to reduce the incidence of contact dermatitis.